Estudo do efeito otoprotetor da dexametasona na ototoxicidade induzida por cisplatina em ratos - Capelo, Isabelle Oliveira Jataí (2017)
Cisplatin (cisdiaminodichloroplatinum) (CDDP) is a chemotherapeutic agent often used in the treatment of several neoplastic lineages. However, ototoxicity continues to be one of the side effects that cause significant morbidity and is responsible for limiting its use. The main objective of this study was to evaluate the protection capacity of dexamethasone against the ototoxicity of cisplatin through the functional evaluations by brainstem evoked response audiometry (BERA) and morphological by optical microscopy. Male Wistar rats were divided into four groups: 1. Control: 06 animals received saline intraperitoneal (IP) 8ml / kg / day for four days; 2. DEXA15 + CDDP: 11 animals received dexamethasone 15mg / kg / day via IP and 90 minutes (min) after 8mg / kg / day of cisplatin via IP for four days; 3. DEXA20 + CDDP: 07 animals received 20 mg / kg / day of dexamethasone via IP and 90 min after 8 mg / kg / day of cisplatin via IP for four days; 4. C + CDDP: 11 animals receive 8ml / kg / day of saline via IP and 90 min after 8mg / kg / day of cisplatin via IP for four days. Based on the results of this study, it was found that dexamethasone did not protect against weight loss of animals exposed to cisplatin; The mortality rate was compatible with the literature; The animals in the DEXA20 + CDDP group had the statistically significant BERA threshold altered; The animals of the groups DEXA15 + CDDP and DEXA20 + CDDP had the vascular stria partially preserved after exposure to cisplatin. It was concluded that dexamethasone at a dose of 15mg / kg / day protected against ototoxicity by cisplatin in functional evaluation by BERA and morphological by optical microscopy, but did not protect against systemic toxicity and that dexamethasone at a dose of 20 mg / kg / day protected against ototoxicity by cisplatin through morphological evaluation, but not by functional evaluation.